Digital Marketing Competency Analysis On MSME Sales Of Indigenous Papuans In Southwest Papua - Maryen, Andrei; Clan, Edward; Patiasina, Rendi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The utilization of digital marketing platforms represents a crucial potential for the growth of Micro, Small, and Medium Enterprises (MSMEs) in facing an increasingly competitive market. Digital marketing entails marketing or promoting a brand or product through the digital or internet sphere. The extensive user base on the internet presents an opportunity to boost sales. However, many challenges confront business practitioners in adapting to technology, such as managing social media. These challenges are encountered by numerous Indigenous Papuan MSMEs in Southwest Papua, primarily due to limited competency in leveraging digital marketing to enhance sales. The research aims to identify the extent to which digital marketing competency influences the sales performance of Indigenous Papuan MSMEs in Southwest Papua. The findings indicate that MSMEs among the Indigenous Papuans in Southwest Papua have yet to achieve a significant level of digital marketing competency. Insufficient understanding and implementation of digital marketing strategies, such as SEO utilization, content analysis, and strong presence in social media, remain primary challenges. This underscores the necessity for further development efforts and education to strengthen digital marketing competency among Indigenous Papuan MSMEs, aiming to maximize their business potential. Furthermore, the relationship between competency and sales reveals suboptimality; a clear correlation exists between the level of digital marketing competency and the sales of Indigenous Papuan MSMEs in the Southwest Province of West Papua. Enhanced implementation of digital marketing strategies can positively influence the sales of these MSMEs, emphasizing the importance of enhancing digital marketing competency as a critical factor in supporting the growth and success of sales among Indigenous Papuan MSMEs in Southwest Papua.